2014
DOI: 10.1310/hpj4903-232
|View full text |Cite
|
Sign up to set email alerts
|

Role of Corticosteroids during Cardiopulmonary Bypass

Abstract: Corticosteroids are commonly used in the peri-operative setting for patients undergoing cardiac surgery with cardiopulmonary bypass (CPB). The infl ammatory response to CPB is associated with organ dysfunction and increased mortality. Corticosteroids reduce biochemical infl ammatory markers associated with CPB, however the impact on clinical outcomes is mixed. The purpose of this article is to evaluate the evidence of changes in clinical outcomes associated with the peri-operative administration of corticoster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…As far as prophylactic use of glucocorticoids during CPB is considered, data in literature are numerous. Most studies, however, show no positive effects of glucocorticoid use on patient clinical outcome [37][38][39]. In the latest meta-analysis on 16, 013 patients, Dvirnik et al [38] concluded that steroid administration at the time of cardiac surgery had an unclear impact on mortality and increased the risk of myocardial injury, and the impact on atrial fibrillation should be viewed with caution given that large trials showed no effect.…”
Section: Discussionmentioning
confidence: 99%
“…As far as prophylactic use of glucocorticoids during CPB is considered, data in literature are numerous. Most studies, however, show no positive effects of glucocorticoid use on patient clinical outcome [37][38][39]. In the latest meta-analysis on 16, 013 patients, Dvirnik et al [38] concluded that steroid administration at the time of cardiac surgery had an unclear impact on mortality and increased the risk of myocardial injury, and the impact on atrial fibrillation should be viewed with caution given that large trials showed no effect.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this trial were in favor of the dexamethasone group as a certain myocardial protection was seen (lower troponin levels) with less requirement for catecholamines. In a recently published comprehensive review of Kristeller et al ( 2014 ) the advantages and disadvantages of corticosteroids have been discussed. They evaluated the results of several studies and found that corticosteroids significantly decreased the incidence of atrial fibrillation, and when applied in low doses also reduced the interval of mechanical ventilation.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanistically, GCs bind cytoplasmic glucocorticoid receptors, and beneficially regulate inflammation and immunosuppression by both transcriptional and non-transcriptional pathways [169]. To reduce inflammation, GCs have been shown to attenuate leukocyte adhesion to the endothelium, and adhesion molecule expression of endothelial cells [200]. Furthermore, GCs reduce cytokine expression at a transcriptional level, and block macrophage/monocyte infiltration [201].…”
Section: Heart Transplantationmentioning
confidence: 99%